Learning While Black: A Culturally Informed Model of the Impostor Phenomenon for Black Graduate Students. (September 2018) - Stone, Steven; Saucer, Chastity; Bailey, Marlon; Garba, Ramya; Hurst, Ashley; Jackson, Stacey M.; Krueger, Nolan; Cokley, Kevin
This study presents a culturally informed model of the impostor phenomenon construct for Black graduate students who attend predominantly White universities. The impostor phenomenon is an internal sense of intellectual fraudulence and a tendency to attribute success to external factors, such as luck. However, the original construct was conceptualized with a sample of White individuals and may not capture the culturally relevant factors for Black graduate students such as race or racial discrimination. Furthermore, only one empirical study investigates impostor feelings in Black graduate students. The current study addresses these gaps by using focus groups to qualitatively investigate the impostor phenomenon in 12 Black graduate students. Inductive thematic analysis revealed five themes ( Awareness of Low Racial Representation, Questioning Intelligence, Expectations, Psychosocial Costs, and Explaining Success Externally ) and multiple subthemes. The findings extend the original construct, contribute to a culturally informed framework for understanding the impostor phenomenon in Black graduate students, and have implications for theory, educators, clinicians, and researchers.